Study on rock mass failure characteristics of double-hole delayed blasting in interbedding based on particle expansion algorithm - Cui, Jianbin; Liu, Xuejun; Xie, Liangfu; Qian, Jiangu (Frontiers in Earth Science, 2023)
The existence of the interface between soft and hard rock often makes it difficult to control the blasting effect. Studying the influence of structural plane and delayed initiation time on rock blasting characteristics can make the blasting effect more controllable. In this paper, by using the Particle Flow Code (PFC2D) and particle expansion algorithm, the double-hole delayed blasting experiments of soft-hard rock are carried out, and the results are analyzed from the perspectives of fragment gradation, micro contact force and energy field. Results show that: (i) When blasting in hard rock, if the distance between structural plane and blasthole is about twice the radius of crushing area, it will easier to form large area fragments, and the fragments tend to be crushed with the increase of distance. When the distance between the structural plane and the blasthole is 2-4 times the radius of crushing area, with the increase of delay time, the overall fragment area value increases first and then decreases, and reaches the maximum when the delay time is 4 ms. (ii) When the structural plane existing in the rock mass, the delayed initiation will make the contact force become relatively uniform within a certain range. The main direction of contact force will appear in the uneven state of contact force generated by simultaneous or delayed initiation, which is close to the parallel or vertical direction of blasthole connection. (iii) When blasting in hard rock, if the distance between the structural plane and the blasthole is greater than about 2 times the radius of the crushing area, compared with simultaneous blasting, the kinetic energy peak and strain energy peak of delayed blasting will be reduced by about 33% and 46%.